Understanding the economic impact of BXW and its management practices in East and Central Africa - Cori, V. di; Kikulwe, Enoch Mutebi; Kozicka, M.; Gotor, Elisabetta (Bioversity International, 2018)
Banana Xanthomonas wilt (BXW) is a widespread banana disease in East and Central Africa (ECA). It has the ability to cause up to 100% yield loss, severely compromising food security and livelihoods for banana-based farming households. There are no BXW-resistant varieties, and cultural management practices offer the only means of control. However, adoption of these practices by farmers has been lower than expected, mainly because of their high cost and labour-intensiveness. There are also other actors, both in public and private sectors, playing an important role in the disease management and facing different costs related to it. Our literature review reveals that a cost analysis of the banana value chain as a whole is missing. By this we mean consideration of not only farmers, who have to sustain the cost of management practices, but also other stakeholders involved, as national and local governments, research institutions and agricultural extensionists. In this study we identify economic actors involved in the banana value chain together with their costs related to the disease management and propose a cost analysis conceptual framework. Further, we review determinants of adoption of the BXW management practices and finally relate them to the estimates of costs of inaction (losses due to BXW spread). In this way, we present a comprehensive picture of costs of BXW spread vis-a-vis the costs of management practices and indicate possible ways to tip the balance in favour of the disease eradication. Ongoing research needs to carry out ex-post analyses on different costs sustained by the stakeholders of banana value chain, and ex ante analyses to predict future scenarios which represent possible alternatives, depending on whether and how the disease will be managed in the coming years. Those results will better inform decision-makers at national, regional, and international levels and provide support in designing strategies to cope with the BXW spread across the ECA region.